2016
DOI: 10.1007/s11746-016-2884-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Lipid Content, Fatty Acid Composition and Nutritional Profiles of Five Freshwater Fish from the Amazon Basin

Abstract: Fish from the Amazon Basin are affected by oscillations in the river water volume, which influences the diet of animal species. This study was aimed at evaluating seasonal variations in lipid content, fatty acid composition and nutritional profiles of five fish species from the Amazon Basin. The lipid contents of all fish species were observed to be lower in flood periods than in drought periods; Brachyplatystoma flavicans showed the largest variation (6.75–15.43 %) between these periods, while Colossoma macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
(57 reference statements)
1
20
2
Order By: Relevance
“…Tropical aquaculture development in Bolivia has mostly focused on pond culture of the indigenous omnivorous fish known locally as "tambaqui" (Piaractus brachypomus) and "pacu" (Colossoma macropomum), or their hybrids (Valladao et al 2016;Vega et al 2018). These fish are robust and easy to grow, and are high in essential amino acids, unsaturated fatty acids, iron, and protein (Murthy et al 2015;Petenuci et al 2016). The fish were identified by the FAO as a promising native alternative to tilapia culture in the late 1970s, and its culture has been perfected in Brazil and neighboring countries.…”
Section: The Central Bolivian Aquaculture Value Chain and Study Areamentioning
confidence: 99%
“…Tropical aquaculture development in Bolivia has mostly focused on pond culture of the indigenous omnivorous fish known locally as "tambaqui" (Piaractus brachypomus) and "pacu" (Colossoma macropomum), or their hybrids (Valladao et al 2016;Vega et al 2018). These fish are robust and easy to grow, and are high in essential amino acids, unsaturated fatty acids, iron, and protein (Murthy et al 2015;Petenuci et al 2016). The fish were identified by the FAO as a promising native alternative to tilapia culture in the late 1970s, and its culture has been perfected in Brazil and neighboring countries.…”
Section: The Central Bolivian Aquaculture Value Chain and Study Areamentioning
confidence: 99%
“…There is general agreement that the composition of polyunsaturated ω-3 and ω-6 fatty acids (PUFAs) in fish tissue varies depending on the fish diet and on factors such as the species, gender, age, size, reproductive status, sexual maturity, feed, water temperature, geographic location and season (Almeida et al, 2009;Ramos-Filho et al, 2010;Petenuci et al, 2016). The present results showed that the freshwater fish species contained a substantial amount of PUFAs with carbon chains ranging from C 18 to C 22 , but that Nile tilapia (pond) and silver carp had very low PUFA contents.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…The benefits of ω3 PUFAs for humans are associated with the synthesis of eicosanoids, such as leukotrienes, prostaglandins and thromboxanes (Souza, 2010;Kuda et al, 2018). Another important aspect is the nutritional value of PUFAs in human metabolism, which can be estimated by way of health 'indicators' that are calculated using empirical equations: the atherogenicity (AI) and thrombogenicity (TI) indexes, and the hypocholesterolemic/hypercholesterolemic (H/H), polyunsaturated/saturated (P/S) fatty acids and omega-3/omega-6 (ω-3/ω-6) ratios (Ulbricht & Southgate, 1991;Šimat et al, 2015;Petenuci et al, 2016). These indices are strongly associated with disease prevention and health promotion (Rhee et al, 2017;Cherifi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained were lower than those reported for some freshwater fish, such as Nile tilapia GIFT (0.67), 55 Tilapia roja (1.42), Barbado (1.18), and Jau (1.00) 55 and fish from the Amazon basin, such as Colossoma macropomum (0.65), Brachyplatystoma filamentosum (0.89) and Brachyplatystoma flavicans (0.89). 56 …”
Section: Fatty Acid Composition -Nile Tilapia Filletsmentioning
confidence: 99%